PENGARUH HERDING DAN LITERASI KEUANGAN ATAS KEPUTUSAN INVESTASI DENGAN DIMODERASI VARIABEL RELIGIUSITAS - Putra, Gilang Kharisma (Fakultas Ekonomi, Universitas Semarang, 2024)
This study aims to examine the influence of herding and financial literacy on investment decisions with religiosity as a moderation variable. Religiosity is the focus of this study which is expected to strengthen the relationship of financial literacy variables to investment decision variables and weaken the relationship of herding variables to investment decision variables. This is considered necessary because it is suspected that investors with aspects of good religiosity allegedly tend not to be speculative and prioritize rationality in their actions. The method used in this study is quantitative method with primary data. Using a purposive sampling approach. With the criteria, respondents must be students of the Faculty of Economics and Business, Selamat Sri University, Kendal regency who are taking investment and portfolio management courses, it was found that the sampling to be used in this study was 98 students. This study used two independent variables, one dependent variable and one moderating variable. Herding and financial literacy were chosen to be independent variables, investment decisions were chosen to be dependent variables while religiosity was chosen to be moderation variables. Data is processed using SEM analysis with smartPLS 4.0 application tools. The results of this study show that the two independent variables, namely financial literacy and herding, have a significant positive effect on investment decisions, while religiosity as a moderation variable has not been able to strengthen or weaken the relationship between exogenous and endogenous variables.